2015
DOI: 10.1523/jneurosci.1087-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of Hippocampal Pathophysiology inSyngap+/−andFmr1−/yMice

Abstract: Previous studies have hypothesized that diverse genetic causes of intellectual disability (ID) and autism spectrum disorders (ASDs) converge on common cellular pathways. Testing this hypothesis requires detailed phenotypic analyses of animal models with genetic mutations that accurately reflect those seen in the human condition (i.e., have structural validity) and which produce phenotypes that mirror ID/ASDs (i.e., have face validity). We show that SynGAP haploinsufficiency, which causes ID with co-occurring A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 40 publications
12
73
0
Order By: Relevance
“…Maturation and size of spines in the hippocampal dentate gyrus of Syngap1 heterozygous mice follow a similar trend to that observed in the somatosensory cortex, although dendritic complexity is not affected in this cortical area [72]. In the hippocampal CA1 of adult mice, the density of mushroom spines, but not those of thin or stubby spines, is increased in Syngap1 +/− mice compared to WT mice [51], although another study using young adult mice reported no change in spine densities or size [22]. Studies using in vitro systems and KO mice have shown that SynGAP expression is inversely correlated to the levels of AMPA receptors, but not NMDA receptors, at the synapse [306].…”
Section: Lessons From Animal Modelsmentioning
confidence: 82%
“…Maturation and size of spines in the hippocampal dentate gyrus of Syngap1 heterozygous mice follow a similar trend to that observed in the somatosensory cortex, although dendritic complexity is not affected in this cortical area [72]. In the hippocampal CA1 of adult mice, the density of mushroom spines, but not those of thin or stubby spines, is increased in Syngap1 +/− mice compared to WT mice [51], although another study using young adult mice reported no change in spine densities or size [22]. Studies using in vitro systems and KO mice have shown that SynGAP expression is inversely correlated to the levels of AMPA receptors, but not NMDA receptors, at the synapse [306].…”
Section: Lessons From Animal Modelsmentioning
confidence: 82%
“…Similarly, hippocampal mGluR-LTD is enhanced in mice with a deletion for the eIF4E–binding protein 2 gene ( Eif4ebp2 ), which encodes 4E-BP2, a suppressor of mRNA translation initiation 123 . Hippocampal mGluR-LTD is furthermore enhanced in Syngap +/− mice 124 . In these mice, extracellular signal-related kinases 1 and 2 (ERK1/2) signaling is enhanced, which may increase eIF4E cap-dependent translation (for review, see ref.…”
Section: Ltd Dysregulation and Synaptic Pruning Deficits In Autismmentioning
confidence: 96%
“…This work suggests that targeting mGlu 5 or its downstream effectors may be a fruitful approach for improving the course of FX and other genetic syndromes with shared pathophysiology (Aguilar-Valles et al, 2015; Auerbach et al, 2011; Barnes et al, 2015; Bozdagi et al, 2010; Tian et al, 2015; Wenger et al, 2016). Indeed, mGlu 5 -based therapies have been immensely successful at correcting FX in animal models (Bhakar et al, 2012).…”
Section: Introductionmentioning
confidence: 94%